READABILITY LEVEL OF READING TEXTS IN THE ENGLISH TEXTBOOK “ENGLISH IN MIND” FOR TENTH GRADE STUDENTS AT SMKN 3 KOTA BENGKULU (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
The objective of the research is to find out the readability level of the texts in English textbook based on Fog Index (FI). This research was categorized as descriptive quantitative research. The object of this research was reading materials English textbook entitled English in Mind Second Edition by Cambridge University Press for tenth grade of Vocational Senior High School. FOG index was used to determine the readability level of the texts based on the average number of sentences and hard words (polysillabic). The finding of this research revealed that the readability of the texts in English in Mind second edition textbook by Cambridge University was easy based on FOG Index (FI) analysis result. Based on FOG Index (FI) analysis result, the percentage of level of readability of English in Mind textbook showed that there were 26 (68%) of texts were easy and 12 (32%) of texts were moderate. Overall, the readability of the texts in English in Mind second edition textbook by Cambridge University was dominantly easy for grade tenth of SMKN 3 Kota Bengkulu. It was suggested for the teachers or the readers to understand readability level of reading materials and know whether the reading materials given to their students are appropriate for them or not.
Keywords: Readability Level; Reading Texts; English Textbook “English in Mind